Baryonic impact on the dark matter orbital properties of Milky Way-sized haloes - Zhu, Qirong; Hernquist, Lars; Marinacci, Federico; Springel, Volker; Li, Yuexing (Monthly notices of the Royal Astronomical Society, 2017)
We study the orbital properties of dark matter haloes by combining a spectral method and cosmological simulations of Milky Way-sized Galaxies. We compare the dynamics and orbits of individual dark matter particles from both hydrodynamic and N-body simulations, and find that the fraction of box, tube and resonant orbits of the dark matter halo decreases significantly due to the effects of baryons. In particular, the central region of the dark matter halo in the hydrodynamic simulation is dominated by regular, short-axis tube orbits, in contrast to the chaotic, box and thin orbits dominant in the N-body run. This leads to a more spherical dark matter halo in the hydrodynamic run compared to a prolate one as commonly seen in the N-body simulations. Furthermore, by using a kernel-based density estimator, we compare the coarse-grained phase-space densities of dark matter haloes in both simulations and find that it is lower by ∼0.5 dex in the hydrodynamic run due to changes in the angular momentum distribution, which indicates that the baryonic process that affects the dark matter is irreversible. Our results imply that baryons play an important role in determining the shape, kinematics and phase-space density of dark matter haloes in galaxies.